2013
DOI: 10.1007/s12017-013-8275-5
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Roles of Trehalose and Hsp104 in the Inhibition of Aggregation of Mutant Huntingtin in a Yeast Model of Huntington’s Disease

Abstract: Despite the significant amount of experimental data available on trehalose, the molecular mechanism responsible for its intracellular stabilising properties has not emerged yet. The repair of cellular homeostasis in many protein-misfolding diseases by trehalose is credited to the disaccharide being an inducer of autophagy, a mechanism by which aggregates of misfolded proteins are cleared by the cell. In this work, we expressed the pathogenic N-terminal fragment of huntingtin in Δnth1 mutant (unable to degrade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…No difference in expression of Hsf1, Hsp26 or Hsp104 was seen in yeast cells expressing 25Q-htt and 103Q-htt (Fig. S3), confirming that the heat shock response is not induced in cells expressing the aggregated protein [22,52]. When the protein expression levels of Hsf1 and Hsp104 were compared across parental and ΔGpd1 cells, significant overexpression of the chaperones was seen in the deletion mutant (Fig.…”
Section: Gpd1 Is a Negative Regulator Of Heat Shock Response In Yeastsupporting
confidence: 53%
“…No difference in expression of Hsf1, Hsp26 or Hsp104 was seen in yeast cells expressing 25Q-htt and 103Q-htt (Fig. S3), confirming that the heat shock response is not induced in cells expressing the aggregated protein [22,52]. When the protein expression levels of Hsf1 and Hsp104 were compared across parental and ΔGpd1 cells, significant overexpression of the chaperones was seen in the deletion mutant (Fig.…”
Section: Gpd1 Is a Negative Regulator Of Heat Shock Response In Yeastsupporting
confidence: 53%
“…Trehalose is shown to protect against hypoxic and anoxic injuries and suppress protein aggregation (44, 75). In vivo findings have revealed that trehalose-induced autophagy may facilitate the clearance of mutant forms of protein aggregates in neurodegenerative disorders such as Huntington and Parkinson diseases in murine models (6, 44, 76, 77). As an autophagy inducer, trehalose may turn on autophagy in an mTOR-independent manner (42).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance-associated myocardial anomalies are reminiscent of those found in diabetic individuals with compromised heart function, characterized by impaired ventricular compliance, prolonged action potential duration and ventricular diastole, and delayed cytosolic Ca 2+ clearance (35). It is suggested that compromised insulin signaling in the heart plays an important role in insulin resistance-induced myocardial contractile and geometric anomalies (6, 7). Within the complex insulin regulatory signaling cascade, the phosphatidylinositol 3-kinase (PI3K)-Akt pathway governs the metabolic properties of insulin and serves as an essential gate-keeper for post-insulin receptor signaling transduction (8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose is an important storage molecule that has been suggested to be a longevity assurance sugar in C. elegans [51] , and is considered to be a stress responsive metabolite. Trehalose has been proposed to play a role against oxidative and osmotic stresses and in protein stabilization [52–54] . As previously described [33,43] , trehalose accumulates to higher levels in daf-2 mutants than in wild type animals in a DAF-16 independent manner [43] .…”
Section: Discussionmentioning
confidence: 99%